All-digital controlled boost DC–DC converter with all-digital DLL-based calibration. Issue 10 (October 2015) - Kao, Shao-Ku; Wu, Jen-Hou; Cheng, Hsiang-Chi
Abstract Traditional digital controls mostly use digital–analog converters to convert input and output voltages into digital coding to achieve control. This paper proposes the use of two digital ramps with two different frequencies to replace a digital–analog converter. This approach can produce seven bit resolution for the DPMW signal. In addition, we use an all-digital DLL phase correction concept to further enhance the resolution of the DPWM signal by an additional three bits, resulting in 10-bit DPWM signal resolution. The proposed circuit uses 0.35 μm CMOS processes, with a core area of 0.987 mm2, a system switching frequency of 500 KHz, an input voltage range of 3.3–4.2 V, and an output voltage range of 5 V. Output voltage measurement accuracy reaches 99%, while the system reaches efficiency of 91% with output loads of up to 500 mA.